Is there a common basis between hiatal hernia and hemorrhoidal disease?. Issue 5 (May 2015) - Sahiner, Zeynep; Uzel, Mehmet; Filik, Levent
Abstract In this letter-to-editor, we hypothesize that there is a link between hemorrhoidal disease and hiatal hernia. We underline common risk factors for both and present a cross-sectional patient data. Therefore, we emphasize the necessity of new studies to clarify this coincidence. Clinical benefit of establishment of this link is to delay or prevent development of hiatal hernia as a result of appropriate preventive measures. Accordingly, postoperative period of hiatal hernia operations may also be relieved or recurrence risk may also be decreased with this precautions.